Propchan: A Mobile Application for Property Management - Yang, Chow Jiunn; Joseph, Minnu Hellen; Salleh, Masrina A. (Journal of Applied Technology and Innovation, 2023)
Tenants, the management team, and the administrator can all monitor and manage their property using the property management system. The current systems have issues with several capabilities, including poorly functioning notifications, a perplexing user interface, bad visitor management, and unclear payment options. To close these gaps and streamline a variety of processes, including management and monitoring, business operations, and management-to-management communication, the Propchan program was created. By applying the in-depth comparison, Dart with the Flutter framework was selected as a back-end programming language. Android Studio is an interactive development environment for developing mobile apps, and VSCode is the IDE for the server. PostgreSQL was chosen as the database management system, and Windows 10 Home Edition was chosen as the operating system. The system development process was implemented using a waterfall model. In future studies, it is necessary to strengthen the security measures of the Propchan program to further secure user confidentiality as well as address the problem with connecting the client to the server in terms of adding data and getting database results.